Human Cytomegalovirus Inhibition by Cardiac Glycosides: Evidence for Involvement of the hERG Gene - Kapoor, Arun (American Society for Microbiology, 2012)
Infection with human cytomegalovirus (HCMV) continues to be a major threat for pregnant women and the immunocompromised population. Although several anti-HCMV therapies are available, the development of new anti-HCMV agents is highly desired. There is growing interest in identifying compounds that might inhibit HCMV by modulating the cellular milieu. Interest in cardiac glycosides (CG), used in patients with congestive heart failure, has increased because of their established anticancer and their suggested antiviral activities. We report that the several CG—digoxin, digitoxin, and ouabain—are potent inhibitors of HCMV at nM concentrations. HCMV inhibition occurred prior to DNA replication, but following binding to its cellular receptors. The levels of immediate early, early, and late viral proteins and cellular NF-κB were significantly reduced in CG-treated cells. The activity of CG in infected cells correlated with the expression of the potassium channel gene, hERG. CMV infection upregulated hERG, whereas CG significantly downregulated its expression. Infection with mouse CMV upregulated mouse ERG (mERG), but treatment with CG did not inhibit virus replication or mERG transcription. These findings suggest that CG may inhibit HCMV by modulating human cellular targets associated with hERG and that these compounds should be studied for their antiviral activities.